PERBEDAAN PENURUNAN NYERI DISMENOREA PADA REMAJA DENGAN TATALAKSANA GUIDED IMAGERY DAN KOMPRES HANGAT - Diah Ulfah Wijayanti; Jupriyono .; Ari Kusmiwiyati (Poltekkes Kemenkes Malang, 2019)
Dysmenorrhoea is pain that accompanies menstruation, with no abnormalities found in the reproductive organs. Management can be done disminorea pharmacological and non pharmacological. One way of non pharmacological treatment is with guided imagery and warm compresses. The research objective was to determine differences in pain reduction of primary dysmenorrhoea in adolescents with treatment of guided imagery and warm compresses. The study design using the design of experiment with design Quasi Non Equivalent Control Group. Population coverage by 45 female students in class X and XI SMA Negri 8 Malang. A sample size of 40 students by using purposive sampling, which are divided into two groups, namely the group of 20 students and 20 female students warm compresses guided imagery group. The research instrument is observation sheet NRS or Numeric Rating Scales. Data were analyzed using the Wilcoxon Signed Rank, Mann Whitney Test namely T approximately same as 0.05. Warm compresses and guided imagery are both contribute in reducing pain. On the Mann Whitney Test, with T approximately 0.05 p value of 0.000, therefore p is smaller than T approximately then there is a significant difference between the provision of guided imagery and warm compresses to the painful decline disminorea.